2013
DOI: 10.1128/genomea.00038-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome of the Solvent-Tolerant Staphylococcus warneri Strain SG1

Abstract: Staphylococcus warneri is a Gram-positive bacterium commonly found in human skin flora. The genome of a laboratory S. warneri isolate, strain SG1, was sequenced to explore its mechanism of solvent tolerance and its potential as a chassis for biofuel production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The first complete genome sequence of S. warneri strain SG1 isolated from a laboratory is reported in 2013, Canada [10]. To date, the full genomes of five S. warneri strains are publicly available in NCBI Genome database (up to March, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first complete genome sequence of S. warneri strain SG1 isolated from a laboratory is reported in 2013, Canada [10]. To date, the full genomes of five S. warneri strains are publicly available in NCBI Genome database (up to March, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A similar plasmid (pvSw4, NCBI access number: NC_020266.1) was identified in S. warneri [ 28 ], which covers 73% and shares 99.48% of similarity with this one.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also identified that the phage φSa3, inserted in the genome of the two other S. argenteus in the β-hemolysin region, is not present in S. argenteus PJI , which results in an intact β-hemolysin gene. [28]). The latter covers 73% and shares 99.48% of similarity with the one we identified in S. argenteus PJI.…”
Section: Genomic Analysis Of Staphylococcus Argenteus Pjimentioning
confidence: 99%
“…The consensus sequences were computationally shredded and reassembled with Phrap version SPS-4.24 (7, 8) to allow some manual editing with Consed (9), resulting in 25 and 67 final contigs of >200 bp (99.50% and 95.89% of the reads), with N 50 values of 480,873 bp and 665,039 bp for SMA0023-04 and SMA0670-05, respectively. These contigs cover 89.26% and 91.77% of the S. warneri SG1 chromosome (GenBank accession number NC_020164), respectively (10), using Mummer alignment version 3.0 (11). The draft genomes of SMA0023-04 and SMA0670-05 consist of 2,466,813- and 2,555,257-bp sequences, with average G+C contents of 32.5% and 32.6%, respectively.…”
Section: Announcementmentioning
confidence: 99%